Belonging and culturally nuanced communication in a refugee early childhood centre in Aotearoa New Zealand. (December 2018) - Mitchell, Linda; Bateman, Amanda
As a concept, 'belonging' is acknowledged to be complex, culturally determined and multifaceted. The processes of supporting belonging through early childhood education, especially where different cultural beliefs require understanding and negotiation, are not well understood. This is certainly the case for refugee children and families within early childhood education in Aotearoa New Zealand. Coming to belong is a particular challenge for these families who have been forcibly displaced from their home country. This article analyses documentation and video and interview data from a research study in an early childhood centre for refugee children and families. The ways in which cultural values and communication modes of gesture, spoken language, voice tone and dance were integrated within the curriculum are examined. A main argument is that pedagogy which incorporates key cultural constructs that refugee families bring with them strengthens a sense of belonging.